Heparin Resistance During and Post-Intravenous Nitroglycerin Infusion: Heparin and nitroglycerin interaction - Mojtahedzadeh, Mojtaba; Khalili, Hossein; Mohagheghi, Ali; Dashti-Khavidaki, Simin (Iranian Journal of Pharmaceutical Sciences, 2005)
Nitroglycerin has been reported to reduce activated partial thromboplastin time (aPTT) values in patients treated with concurrent heparin and nitroglycerin. However, studies have yielded conflicting results. To determine whether intravenous nitroglycerin alters the anticoagulant effect of heparin, we prospectively evaluated twenty patients admitted for coronary angioplasty by measuring their aPTT both before initiation and after addition of nitroglycerin to heparin therapy. The results showed that the mean of aPTT at the baseline when patients were on heparin alone was not significantly different from aPTT measured upon addition of nitroglycerin, and 30 min following the cessation of nitroglycerin infusion, when patients were still on the same dose of heparin. Therefore, no direct effect of nitroglycerin on the anticoagulant effect of heparin was observed in this study.